Functionalised-biomatrix for wound healing and cutaneous regeneration: future impactful medical products in clinical translation and precision medicine - Fadilah, Nur Izzah Md; Riha, Shaima Maliha; Mazlan, Zawani; Wen, Adzim Poh Yuen; Hao, Looi Qi; Joseph, Blessy; Maarof, Manira; Thomas, Sabu; Motta, Antonella; Fauzi, Mh Busra (Frontiers in Bioengineering and Biotechnology, 2023)
Skin tissue engineering possesses great promise in providing successful wound injury and tissue loss treatments that current methods cannot treat or achieve a satisfactory clinical outcome. A major direction in the field is to explore bioscaffolds with multifunctional properties to enhance biological performance and expedite complex skin tissue regeneration. Multifunctional bioscaffolds are three-dimensional (3D) constructs manufactured from natural and synthetic biomaterials using cutting-edge tissue fabrication techniques incorporated with cells, growth factors, secretomes, antibacterial compounds, and bioactive molecules. It offers a physical, chemical, and biological environment with a biomimetic framework to direct cells toward higher-order tissue regeneration during wound healing. Multifunctional bioscaffolds are a promising possibility for skin regeneration because of the variety of structures they provide and the capacity to customise the chemistry of their surfaces, which allows for regulated distribution of bioactive chemicals or cells. This review stipulates the wound healing processes used by commercially available engineered skin replacements (ESS), highlighting the demand for a multifunctional, and next-generation ESS replacement. This work also scrutinise the use of multifunctional bioscaffolds in wound healing applications, demonstrating successful biological performance in the in vitro and in vivo animal models, requiring new viewpoints and technological innovations for the clinical application of multifunctional bioscaffolds for wound healing.